Knowledge of the multidisciplinary team on patient safety in an Intensive Care Unit: 10.15343/0104-7809.202246587597I - Gomes, Renara Meira (2022)
The aim of this study was to analyze the factors that interfere with patient safety in Intensive Care Units (ICU) through the knowledge of the multidisciplinary team. This was a descriptive study with a quantitative and qualitative approach, carried out with 40 health professionals, who make up the multidisciplinary team of the ICU of a regional reference hospital of the state. Data collection was carried out between the months of May and December 2020. It took place through a semi-structured interview, guided by a thematic script and a sociodemographic questionnaire. Data were processed using IRAMUTEQ software, through Descending Hierarchical Classification, and were analyzed using the collective subject discourse technique. It was demonstrated that the lack of knowledge about the concept of patient safety, the lack of care protocols, interpersonal problems, the occurrence of adverse events, underreporting, and inadequate estimations are some of the factors that interfere with patient safety in the ICU. There is a need to resolve existing flaws, especially regarding personnel size, issues related to the interaction of the multidisciplinary team, and the implementation of institutional protocols, which guide care. By strengthening the safety culture, professionals feel empowered to report not only AEs, but also reportable circumstances.